Strategic Considerations in Auditing - Fellingham, John C.; Newman, D. Paul (The Accounting Review, 1985)
[A simplified audit setting is used to illustrate the crucial nature of strategic interactions in audit planning and in assessing audit risk. Unlike single-person decision-theoretic models which essentially represent games against nature, the model developed here allows a prospective audit to influence the behavior of the auditee. We reformulate the problem in a game-theoretic framework with rational players which (1) encompasses strategic factors for both the auditor and auditee, (2) is consistent with behavioral hypotheses regarding the effect of an audit, and (3) is consistent with certain audit phenomena such as randomized strategies. An illustration is provided which demonstrates several points. First, both the auditor and the auditee may frequently use a randomized strategy. Second, the auditor's strategy depends on the interaction between the accounting control system and the auditee's actions. In addition, the use of traditional single-person decision theory may frequently cause errors in estimating audit risk because it fails to consider audit influences on the auditee. Settings in which decision theory may serve as an adequate model simplification are also considered.]